2010
DOI: 10.3354/ab00280
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by the Formosan landlocked salmon Oncorhynchus masou formosanus

Abstract: The critically endangered Formosan landlocked salmon Oncorhynchus masou formosanus is one of the southernmost natural salmon populations in the world, which only occurs in Chichiawan Stream and its tributaries in the Wuling basin of subtropical Taiwan. We examined habitat uses by different size classes of the Formosan salmon and the sympatric shovelmouth minnow Varicorhinus barbatulus, and identified the relative importance of environmental variables, biotic components and seasonal effects in explaining the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Habitat uses by salmon and the sympatric shovelmouth minnow were distinct. Hsu et al (2010) discovered that Formosan salmon used habitats which were subject to lower temperatures and were distributed in reaches at higher elevations than those of shovelmouth minnow. The diet composition matrix also demonstrated that the Formosan salmon is insectivorous, whereas the shovelmouth minnow relies heavily on algae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Habitat uses by salmon and the sympatric shovelmouth minnow were distinct. Hsu et al (2010) discovered that Formosan salmon used habitats which were subject to lower temperatures and were distributed in reaches at higher elevations than those of shovelmouth minnow. The diet composition matrix also demonstrated that the Formosan salmon is insectivorous, whereas the shovelmouth minnow relies heavily on algae.…”
Section: Discussionmentioning
confidence: 99%
“…Riffles are the major habitat in Chichiawan Stream and comprise > 80% of the stream area (Lin et al 2006 in the wet season (Hsu et al 2010). Consequently, the streambed consists of a high proportion of pebbles (42%) in the dry season (winter), but is dominated by rubble (26%) and boulders (21%) in the wet season (summer) (Lin et al 2006 inputs on downstream water quality and epilithic algae is significant (Yu & Lin 2009).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Streambed composition varied seasonally, consisting mainly of 39% pebbles and 27% cobbles in the dry season and 44% boulders in the wet season. The catchment of the KSS is covered by natural forests, and no agricultural activity occurs along the stream (Yu and Lin 2009;Hsu et al 2010). The YSS is located downstream of the CCWS and is 11.4 km long with a mean gradient of 68 m km À1 and a catchment area of 31 km 2 .…”
Section: Study Sitementioning
confidence: 99%
“…The landlocked salmon of Taiwan, Oncorhynchus masou formosanus (Jordan & Oshima 1919), was listed as Critically Endangered by the IUCN in 1996 (Kottelat 1996), which only distributed in the upstream of Dajia River (Hsu et al 2010). The total number of O. m. formosanus has increased from 200 to around 3000 through the efforts of repopulation and habitat recovery (Chung et al 2008).…”
mentioning
confidence: 99%